Rare earth doped strong neutral medicinal glass and preparation method thereof

By introducing lanthanum oxide and yttrium oxide into the medicinal glass, the chemical stability and structural tightness of the glass are improved, and the problem that existing medicinal glasses are difficult to take into account both acid resistance, alkali resistance and water resistance, achieving efficient preparation and excellent performance of strong neutral medicinal glasses.

CN119774877APending Publication Date: 2025-04-08AVIC (HAINAN) SPECIAL GLASS TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411961558.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

It is difficult to take into account the three-level 1 properties of acid resistance, alkali resistance and water resistance at the same time, and it has a long melting time, high energy consumption and high raw material costs.

Method used

Using rare earth-doped strong neutral medicinal glass, the chemical stability and structural tightness of the glass are improved by introducing lanthanum oxide and yttrium oxide into the glass network, the melting temperature and viscosity are reduced, and the melting process is simplified.

Benefits of technology

It has achieved strong neutral properties of medicinal glass with three levels of acid resistance, alkali resistance and water resistance, shortened melting time, saved energy, reduced raw material costs, and was suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005217284060000041
    Figure BDA0005217284060000041
  • Figure BDA0005217284060000051
    Figure BDA0005217284060000051
Patent Text Reader

Abstract

The invention provides rare earth doped strong neutral medicinal glass and a preparation method thereof, and the rare earth doped strong neutral medicinal glass comprises the following raw materials in parts by weight: 68-72 parts of silica sand, 16.5-18.5 parts of anhydrous borax, 4.5-5.5 parts of aluminum oxide, 1.5-2.0 parts of limestone, 0.8-2.0 parts of yttrium oxide, 1.8-4.0 parts of sodium carbonate, 0-1.5 parts of potassium carbonate, 0.5-1.5 parts of a lanthanum oxide-barium carbonate mixture and 0.2-0.4 part of sodium chloride. The medicinal glass provided by the invention has strong neutral properties of three first-level acid resistance, alkali resistance and water resistance, and has a relatively low average linear thermal expansion coefficient (alpha 35-300 DEG C lt; 5.30 * 10 <-6 > K <-1 >) and relatively high bending strength (sigma fgt; 180 MPa) and the like. And meanwhile, the preparation and melting time is short, the cost is lower, the process is simple, and the method is suitable for actual mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pharmaceutical glass, and in particular to a rare earth-doped strongly neutral pharmaceutical glass and a preparation method thereof. Background Art

[0002] Glass containers used for drug packaging are in direct contact with drugs for a long time. Drugs have different acid and alkali corrosiveness. Long-term contact will produce a small amount of chemical reaction through exchange, corrosion, and adsorption between surfaces, thus affecting the performance of the drugs themselves. In severe cases, the inner surface of the glass packaging material may even peel off, forming fine solid particles, which may cause serious consequences once introduced into the human body. Borosilicate glass has incomparable advantages over other glass products in terms of water resistance, acid resistance, alkali resistance and strength.

[0003] Medium borosilicate 5.0 glass is a common neutral pharmaceutical glass in the international market. However, due to its difficult production technology and high investment, the international market is currently mainly controlled by several large companies such as Germany's Schott and Corning, and their production capacity accounts for about 80% of the total.

[0004] The pharmaceutical glass packaging containers that my country has been producing and using for a long time are called "semi-neutral borosilicate pharmaceutical glass" products in the industry. The expansion coefficient of this glass is 7.0×10 -6 / ℃, also called "7.0 glass", its chemical stability does not meet the neutral requirements, its 121℃ particle water resistance and surface water resistance are usually between 1 and 2 levels, which cannot meet the requirements of first-level water-resistant glass; when containing sensitive drugs, the acid and alkaline substances in the glass are very easy to precipitate, and in severe cases, the glass may fall off, thus affecting the quality of the drugs. This has a potential safety hazard for the use of drugs that are acidic, alkaline, or sensitive to pH, which is one of the main reasons why my country's pharmaceutical glass has long relied on imports.

[0005] In order to change this situation, it is necessary to conduct further research and development on pharmaceutical glass.

[0006] In terms of the performance indicators of pharmaceutical glass, its acid resistance and alkali resistance are often a contradiction. Currently, there are few products on the market that can simultaneously meet the three levels of acid resistance, alkali resistance and water resistance.

[0007] Chinese patent CN201410448955.3 discloses a neutral borosilicate glass and its application, wherein the glass composition by weight percentage is: SiO2 70.0-80.0%, B2O3 7.0-12.0%, Al2O3 1.5-5.0%, Na2O 5.5-8.0%, K2O 0-1.0%, Li2O 0-1.5%, CaO 1.5-3.0%, BaO 0-3.5%, MgO 0-2.0%, NaCl 0.3-0.5%, Na2O+K2O+Li2O 6.0-9.5%, CaO+BaO+MgO 1.5-6%. The neutral borosilicate glass has a water resistance of level 1 at 98°C particle method, a water resistance of level 1 at 121°C particle method, and a acid resistance of level 1, but only a level 2 alkali resistance. In addition, during implementation, the batch material is heated from room temperature to 1650°C at a heating rate of 5°C / min and then clarified for 4 hours, which results in problems such as too high melting temperature and too long processing time.

[0008] Chinese patent CN201811314131.1 discloses a neutral borosilicate pharmaceutical glass and a preparation method thereof, wherein the raw materials are composed of 57-66 parts by weight of quartz sand, 4.5-6.8 parts of aluminum hydroxide, 20-26 parts of borax pentahydrate, 0-4 parts of soda ash, 1.9-5 parts of barium nitrate, 1.5-4 parts of calcite, 2-4 parts of potassium carbonate, 1.5-5 parts of salt, 0-5 parts of manganese dioxide, 0.1-0.3 parts of lithium carbonate, 0.1-0.3 parts of cerium oxide, 0.1-0.4 parts of zinc oxide, 0<cesium carbonate≤0.5 parts, 0<indium carbonate≤0.3 parts, and 0<sodium selenate≤0.2 parts. Although this pharmaceutical glass is alkali-resistant and the glass particles at 98°C and 121°C are water-resistant to level 1, its acid resistance is unknown. Its melting time is no less than 4 hours, and relatively expensive raw materials such as cesium and indium are used, so the preparation cost is relatively high.

[0009] Chinese patent CN202311356573.3 discloses a neutral borosilicate glass medicinal tube and its preparation method, the glass raw material composition weight parts are: 65-67 parts of quartz sand, 27-29 parts of borax, 3.5-5.5 parts of aluminum hydroxide, 1.8-2.0 parts of wollastonite, 6-8 parts of nepheline, 1.5-1.8 parts of diopside, 7-9 parts of spodumene, 1.2-1.5 parts of zirconium oxide, 0.8-1.0 parts of yttrium trioxide, 0.6-0.8 parts of pretreated red mud, 1.6-1.8 parts of sodium fluorosilicate. The 98℃ and 121℃ glass particles of the medicinal glass tube have a water resistance of level 1 and an alkali resistance of level 1, but the acid resistance is unknown, and the time for melting, clarifying and homogenizing is up to 6 hours.

[0010] A comprehensive comparison shows that the currently disclosed neutral pharmaceutical glasses generally have problems such as long melting time, high energy consumption or high raw material cost, and are more or less acidic or alkaline, and cannot simultaneously meet the strong neutrality requirements of level 1 for acid resistance, alkali resistance and water resistance.

[0011] Therefore, it is of great significance to research and develop a strong neutral pharmaceutical glass tube that can simultaneously meet the three properties of acid resistance, alkali resistance and water resistance at level 1, with low raw material cost and uncomplicated melting process. It is in line with the industry development trend and market demand and has good application prospects. Summary of the invention

[0012] In view of this, the purpose of the present invention is to propose a rare earth doped strongly neutral pharmaceutical glass and a preparation method thereof, so as to solve the problems that the existing pharmaceutical glass is difficult to simultaneously take into account the three properties of acid resistance, alkali resistance and water resistance, as well as the difficulty in melting and high production cost.

[0013] The technical solution of the present invention is achieved in this way:

[0014] One of the purposes of the present invention is to provide a rare earth-doped strong neutral pharmaceutical glass, which comprises the following raw materials, by weight: 68-72 parts of silica sand, 16.5-18.5 parts of anhydrous borax, 4.5-5.5 parts of aluminum oxide, 1.5-2.0 parts of limestone, 0.8-2.0 parts of yttrium oxide, 1.8-4.0 parts of soda ash, 0-1.5 parts of potassium carbonate, 0.5-1.5 parts of lanthanum oxide-barium carbonate mixture and 0.2-0.4 parts of sodium chloride.

[0015] Furthermore, the following raw materials are included, by weight: 70.2 parts of silica sand, 17.5 parts of anhydrous borax, 5.0 parts of aluminum oxide, 1.75 parts of limestone, 1.0 parts of yttrium oxide, 2.0 parts of soda ash, 1.4 parts of potassium carbonate, 0.9 parts of lanthanum oxide-barium carbonate mixture and 0.3 parts of sodium chloride.

[0016] In the raw material components of the rare earth doped strong neutral pharmaceutical glass of the present invention, the doped rare earth oxides are lanthanum oxide and yttrium oxide. 3+ and La 3+ Located in the gaps of the glass network, it has a higher field strength and can promote the transformation of [BO3] triangles to [BO4] tetrahedrons, making the glass network structure more compact.

[0017] Among them, the doping of yttrium oxide reduces the amount of non-bridging oxygen in the glass network structure, while increasing the stability of the glass structure, it also significantly improves the alkali resistance of the glass; but when added in excess, Y2O3 will force the bridging oxygen bonds in the glass structure to break, thereby reducing the stability of the glass network structure and increasing the content of isolated hydroxyl groups, thereby reducing its acid resistance.

[0018] The introduction of La2O3 and BaO into the glass by the lanthanum oxide-barium carbonate mixture can increase the strength of the glass, improve the chemical stability of the glass, and effectively reduce the viscosity and melting temperature of the glass, shortening the glass melting time.

[0019] Furthermore, in the lanthanum oxide-barium carbonate mixture, lanthanum oxide and barium carbonate are mixed in any proportion; and the potassium carbonate is anhydrous potassium carbonate.

[0020] Furthermore, the mass ratio of the lanthanum oxide to the barium carbonate is 1:8.

[0021] The second object of the present invention is to propose a method for preparing the above-mentioned rare earth-doped strong neutral pharmaceutical glass, which comprises the following steps: weighing the raw materials by weight and mixing them evenly; placing them in a high-temperature furnace at 1450°C, keeping them warm for 20 minutes for preliminary melting, then heating them to 1610-1620°C at a heating rate of 10°C / min, keeping them warm for 2 hours for clarification and homogenization. Then, the molten glass liquid is poured into a mold for forming, and transferred to an annealing furnace at 600°C, and directly annealed to room temperature, so as to obtain the above-mentioned strong neutral pharmaceutical glass.

[0022] Furthermore, the initial melting temperature is 1450° C. and the holding time is 20 minutes.

[0023] Furthermore, the clarification and homogenization temperature is 1610-1620°C, and the holding time is 2 hours; the annealing temperature is 600°C, and is directly reduced to room temperature in the furnace.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) Currently, the disclosed pharmaceutical glasses rarely have both alkali resistance and acid resistance reaching level 1, and it is even more difficult to meet the strong neutrality requirements of level 1 for acid resistance, alkali resistance, and water resistance. The strong neutral pharmaceutical glass of the present invention not only meets the performance requirements of level 1 for acid resistance, alkali resistance, and water resistance, but also has a lower linear expansion coefficient and higher bending strength, and has excellent comprehensive performance.

[0026] (2) The existing methods for melting medicinal glass generally have the problems of difficulty in melting and clarifying, long melting time, and high energy and raw material costs. However, the strongly neutral medicinal glass of the present invention greatly shortens the time for melting, clarifying, and homogenizing, which not only reduces the volatilization of boron, but also saves energy. In addition, the raw materials used are easily available, the melting process is simple, and it is suitable for large-scale mass production.

[0027] (3) The strong neutral pharmaceutical glass of the present invention is innovatively doped with common rare earth oxides, which effectively improves its melt viscosity, shortens the melting time, and significantly improves its chemical stability.

[0028] As described above, the present invention achieves the strong neutral performance of pharmaceutical glass with level 1 acid resistance, alkali resistance and water resistance through composition design and process optimization, which can fully meet the higher requirements of glass neutrality for drug packaging; and its preparation process effectively shortens the melting time, simplifies the melting process, has low cost, and can achieve large-scale mass production. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0030] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0031] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0032] Example

[0033] The formulas of the rare earth doped strong neutral pharmaceutical glass in various embodiments and comparative examples are shown in Table 1 below:

[0034] Table 1 Composition and control requirements of each embodiment and comparative example (unit: part)

[0035]

[0036] The preparation method of the rare earth-doped pharmaceutical glass comprises the following specific steps:

[0037] (a) Ingredients

[0038] Weigh the raw materials according to the formula in Table 1 and mix them evenly as the batch material.

[0039] (b) Melting

[0040] The above batch materials were placed in a high-temperature furnace at 1450°C, kept warm for 20 minutes for preliminary melting, then heated to 1610-1620°C at a heating rate of 10°C / min, kept warm for 2 hours for clarification and homogenization to obtain molten glass liquid.

[0041] (c) Forming and annealing

[0042] The molten glass liquid is poured into a mold to form, and then transferred to an annealing furnace at 600° C. and directly annealed to room temperature to obtain the pharmaceutical glass.

[0043] Test Case

[0044] The samples prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were tested, and the acid resistance was tested according to "YBB00342004-2015 Determination of glass resistance to boiling hydrochloric acid erosion", the alkali resistance was tested according to "YBB00352004-2015 Determination of glass resistance to boiling mixed alkali aqueous solution erosion", the water resistance of 98°C glass particles was tested according to "YBB00362004-2015 Determination and classification of water resistance of glass particles at 98°C", the water resistance of 121°C glass particles was tested according to "GB / T 12416.2-1990 Test method and classification of water resistance of glass particles at 121°C", the average linear thermal expansion coefficient was tested according to "YBB00202003-2015 Determination of average linear thermal expansion coefficient"; the flexural strength was tested according to "GB / T 6569-2006 Test method for flexural strength of fine ceramics"; some of the results obtained are shown in Table 2.

[0045] Table 2 Performance parameters of the pharmaceutical glass prepared in each embodiment and comparative example

[0046]

[0047] From the data of the examples in Table 2, it can be seen that the pharmaceutical glasses of Examples 1-5 of the present invention have a grade 1 acid resistance, a grade 1 alkali resistance, a grade 1 water resistance of glass particles at 121°C, and a low expansion (α 35-300℃ <5.30×10 -6 K -1 ), high bending strength (σ f >180MPa) and other characteristics.

[0048] When other raw material components do not change much, compared with Example 3, Comparative Example 1 does not add yttrium oxide. Although the prepared pharmaceutical glass has better acid resistance, its alkali resistance is directly reduced to Level 2.

[0049] Compared with Example 1, the amount of yttrium oxide in Comparative Example 2 is directly increased from 1.4 parts to 2.4 parts. Although the prepared pharmaceutical glass has better alkali resistance, its acid resistance is reduced to level 2.

[0050] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.

Claims

1. A rare earth doped strong neutral pharmaceutical glass, characterized in that: The raw materials are as follows, measured by weight: 68-72 parts of silica sand, 16.5-18.5 parts of anhydrous borax, 4.5-5.5 parts of aluminum oxide, 1.5-2.0 parts of limestone, 0.8-2.0 parts of yttrium oxide, 1.8-4.0 parts of soda ash, 0-1.5 parts of potassium carbonate, 0.5-1.5 parts of a mixture of lanthanum oxide and barium carbonate and 0.2-0.4 parts of sodium chloride.

2. The rare earth doped strong neutral pharmaceutical glass according to claim 1, characterized in that: The raw materials are as follows, in parts by weight: 70.2 parts of silica sand; 17.5 parts of anhydrous borax; 5.0 parts of aluminum oxide; 1.75 parts of limestone; 1.0 parts of yttrium oxide; 2.0 parts of soda ash; 1.4 parts of anhydrous potassium carbonate; 0.9 parts of a lanthanum oxide-barium carbonate mixture and 0.3 parts of sodium chloride.

3. The rare earth doped strong neutral pharmaceutical glass according to claim 1, characterized in that: In the lanthanum oxide-barium carbonate mixture, lanthanum oxide and barium carbonate are mixed in any proportion; and the potassium carbonate is anhydrous potassium carbonate.

4. The rare earth doped strong neutral pharmaceutical glass according to claim 2, characterized in that: The mass ratio of the lanthanum oxide to the barium carbonate is 1:

8.

5. The method for preparing the rare earth doped strong neutral pharmaceutical glass according to any one of claims 1 to 4, characterized in that: The process comprises the following steps: weighing the raw materials by weight and mixing them evenly; placing them in a high-temperature furnace at 1450°C, keeping them warm for 20 minutes for preliminary melting, then heating them to 1610-1620°C at a heating rate of 10°C / min, keeping them warm for 2 hours for clarification and homogenization. Then, the molten glass liquid is poured into a mold for forming, and transferred to an annealing furnace at 600°C, and directly annealed to room temperature, thereby obtaining the strong neutral pharmaceutical glass.

6. The method for preparing the rare earth doped strong neutral pharmaceutical glass according to claim 5, characterized in that: The initial melting temperature is 1450°C and the holding time is 20 minutes.

7. The method for preparing the rare earth doped strong neutral pharmaceutical glass according to claim 5, characterized in that: The clarification and homogenization temperature is 1610-1620° C., and the holding time is 2 hours; the annealing temperature is 600° C., and is directly cooled to room temperature in the furnace.

Citation Information

Patent Citations

  • Medium borosilicate glass composition as well as preparation method and application thereof

    CN114507010A

  • Borosilicate glass curing auxiliary agent for treating medium and low-radioactivity waste liquid and use method of borosilicate glass curing auxiliary agent

    CN116813197A

  • Borsilicate glass compositions and uses thereof

    US20040152580A1

  • Fused quartz tubing for pharmaceutical packaging

    US20120148770A1

  • Borosilicate glass with high chemical resistance and application thereof

    US20190322569A1